Government bureaucrats and ethical conduct in Nigeria’s fourth republic: Implications for good governance - Samuel Oni; Celestine Okwudili Abasili; Moyosoluwa Dele-Dada; Charles Osarumwense (Faculty of Social and Political Science, Universitas Airlangga, 2022)
The recognition that ethical conduct is fundamental to accountability, transparency, fairness, equity, and quality service delivery which are the cornerstones of good governance is the reason for rules and regulations in the Nigerian government’s bureaucracy. This governmental administrative machinery, however, continues to face a crucial challenge of inefficiency and unethical practices. This study interrogates how ethical conducts in Nigerian Civil Service have impacted the country’s quest for good governance. The study anchors on the Weberian bureaucratic theory and engaged secondary data from fifty-one (51) articles gathered and analyzed using systematic review (SR) conducted between August 2021 and February, 2022. Findings reveal the misdemeanor and objectionable manifestations among civil servants despite legal instruments, efforts and reforms by the various successive governments aimed at repositioning it for effective and efficient service delivery. The consequence is the continuous weakening of public institutions, collapse of infrastructures, public distrust of government agencies and a sense of despair by the public. The study argues that building a vibrant civil society through public enlightenment and active and independent media is necessary to perform the crucial oversight role on civil servants in the country. This is pivotal to achieving the much needed good governance in the country.